PENGELOLAAN PROGRAM PENGAWASAN PENDIDIKAN AGAMA ISLAM DI LINGKUNGAN KEMENTERIAN AGAMA KABUPATEN PAMEKASAN - Saiful Arif (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2019)
The study describes the management of Islamic education supervision program in the ministry of religious affair at Pamekasan regency. There are three problems to be focus of this study, they are (1) how is arrangement of Islamic education supervision program in the ministry of religious affair at Pamekasan regency. (2) how is the implementation of Islamic education supervision program in the ministry of religious affair at Pamekasan regency? (3) how is evaluation of the implementation of Islamic education supervision program in the ministry of religious affair at Pamekasan regency? To investigate those problems, this study makes use of qualitative approach with descriptive analysis paradigm. The techniques of collecting data are in the form of structured interview,participant observation and documentation analysis. Meanwhile, checking the validity of data is conducted through extention of participation, meticulous observation, triangulation and peer checking.